High-dispersion Co-Fe-NC electrocatalyst based on leaf-shaped zeolite imidazole framework for oxygen-reduction reaction in acidic medium - Im, Kyungmin; Nguyen Quoc Hao; Lee, Eungjun; Lee, Dong Wook; Kim, Jinsoo; Yoo, Sung Jong (WILEY, 2021)
Platinum-free electrocatalysts for oxygen-reduction reactions in acidic medium are challenging as the cathode of PEMFC. Here, we synthesized core-shell-type leaf-shaped CoFe-NC (L-CoFe-NC) catalysts using 2D ZIFs as cores and 3D ZIFs as shells. The amounts of Co and Fe were carefully controlled to obtain highly dispersed CoFe-doped carbon. This strategy made it easy to tune the catalyst while maintaining the advantages of the 2D structures. The prepared L-CoFe-NC showed a half-wave potential (E-1/2) of 0.77 V and an onset potential (E-onset) of 0.88 V in 0.5 M H2SO4. In addition, the results confirmed high durability even after 10 000 tests while retaining excellent performance. This outstanding stability was achieved owing to the high dispersion of Co and Fe in the 2D carbon frame. Furthermore, PEMFC was evaluated using an MEA containing L-CoFe-NC catalysts as a cathode.